The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/admi.202101965
|View full text |Cite
|
Sign up to set email alerts
|

Photoresponsive Polymer Films with Directly Micropatternable Surfaces Based on the Change in Free Volume by Photo‐Crosslinking

Abstract: micropatterns are generated by selectively exposing photoreactive or photoresponsive polymer films to ultraviolet (UV) light in a photo-crosslinking or photodecomposition process and subsequently dissolving the selected areas of the film surfaces using an appropriate solvent. Photo lithography is widely employed as a high-resolution technique because it is suitable for large-area surface patterning with good alignment. However, it is not cost-effective because of the requirement of some complicated processes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
(92 reference statements)
0
5
0
Order By: Relevance
“…The synthesis of 2-cinnamoyloxyethyl methacrylate (CEMA) and PCEMA-g-PDMS has been described in detail in a previous paper as shown in Scheme S1. [37] Successful synthesis was confirmed via proton nuclear magnetic resonance ( 1 H NMR, Figure S1). 1 H NMR spectra were recorded on a GSX-400 NMR instrument (JEOL) operating at 400 MHz with deuterated chloroform (CDCl 3 -d) as the solvent and tetramethylsilane as the internal standard.…”
Section: Preparation Of Photocrosslinkable Polymer Filmsmentioning
confidence: 99%
See 2 more Smart Citations
“…The synthesis of 2-cinnamoyloxyethyl methacrylate (CEMA) and PCEMA-g-PDMS has been described in detail in a previous paper as shown in Scheme S1. [37] Successful synthesis was confirmed via proton nuclear magnetic resonance ( 1 H NMR, Figure S1). 1 H NMR spectra were recorded on a GSX-400 NMR instrument (JEOL) operating at 400 MHz with deuterated chloroform (CDCl 3 -d) as the solvent and tetramethylsilane as the internal standard.…”
Section: Preparation Of Photocrosslinkable Polymer Filmsmentioning
confidence: 99%
“…In our previous study, X-ray photoelectron spectroscopy (XPS) and contact angle measurements revealed that the surface of PCEMA-g-PDMS films underwent no change in chemical properties, such as surface composition and hydrophilicity, upon UV exposure. [37] Therefore, fibronectin may recognize changes in the chemical properties of PCEMA-g-PDMS films due to UV exposure, which are too small to be detected via XPS and water contact angle measurements. However, more cells generally tend to adhere to surfaces on which more fibronectin is adsorbed.…”
Section: Effect Of Uv Exposure On Physical and Chemical Properties Of...mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, quartz molds, while also utilized in nanoimprint lithography, may exhibit fragility and reduced durability compared to silicon molds. 5,10,32 This can affect their longevity and cost-effectiveness for industrial use. Nonetheless, the choice between silicon and quartz molds oen boils down to a trade-off between initial cost and the long-term benets of durability and precision.…”
Section: Introductionmentioning
confidence: 99%
“…Photodimerization occurs when a photodimerizable molecule in its ground state, such as cinnamoyl [ 38 , 39 ], maleimide [ 40 , 41 ], coumarin [ 42 ], and anthracene [ 43 ], is excited by light to form a dimer. We fabricated photoresponsive polymer films by introducing cinnamoyl groups into polydimethylsiloxane with a large free volume and photo-crosslinking only the UV-irradiated regions [ 44 ]. Photodimerization has also been utilized for forming PEG-based hydrogels for cell culture [ 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%